Show what you know. (May 2017) - Brown, Dan; Rhodes, Dwight E.
Educators Rising, an initiative of PDK International, has developed five microcredentials that allow aspiring teachers to demonstrate what they know and are able to do through experiences very similar to what professional teachers do every day .